Writing Wisdom, Reviewing Identity: Positive Outcomes of Participating in a Memoir Course for Older Adults - Bivona, Marissa A.; Kahlbaugh, Patricia E.; Budnick, Christopher J. (The International Journal of Reminiscence and Life Review, 2020)
Constructing a personal narrative and consolidating identity is an ongoing process that becomes pressing in the face of mortality. The current pilot study examined the process of life review in a sample of older people, specifically examining the effects of participation in a memoir course on wisdom, identity, and well-being. We hypothesized that wisdom, identity fidelity and coherence, and subjective well-being would increase for those in the memoir group compared to a control. Eighteen elderly individuals from two senior retirement communities were randomly assigned to participate in weekly classes, for four weeks, either to work on a memoir or discuss films (control group). After engaging in the process of organizing their life story and writing about important memories, the nine individuals in the memoir group scored significantly higher on self-report measures of wise reminiscence, identity fidelity, and subjective well-being compared to those in the control group. Furthermore, exploratory analyses found that wise reminiscence statistically mediated relationships between the memoir condition and the outcome measures of identity fidelity, identity coherence, and subjective well-being. These findings point to the benefits of memoir writing for positive aging as well as potential mechanisms underlying its effectiveness.
Number: 1
Keywords: Identity; Life Review; Narrative; Subjective Well-Being; Wisdom; dept.psy

The Promise of Automated Home-Cage Monitoring in Improving Translational Utility of Psychiatric Research in Rodents. - Mingrone, Alfred; Kaffman, Ayal; Kaffman, Arie (Frontiers in neuroscience, 2020)
Large number of promising preclinical psychiatric studies in rodents later fail in clinical trials, raising concerns about the efficacy of this approach to generate novel pharmacological interventions. In this mini-review we argue that over-reliance on behavioral tests that are brief and highly sensitive to external factors play a critical role in this failure and propose that automated home-cage monitoring offers several advantages that will increase the translational utility of preclinical psychiatric research in rodents. We describe three of the most commonly used approaches for automated home cage monitoring in rodents [e.g., operant wall systems (OWS), computerized visual systems (CVS), and automatic motion sensors (AMS)] and review several commercially available systems that integrate the different approaches. Specific examples that demonstrate the advantages of automated home-cage monitoring over traditional tests of anxiety, depression, cognition, and addiction-like behaviors are highlighted. We conclude with recommendations on how to further expand this promising line of preclinical research. Copyright © 2020 Mingrone, Kaffman and Kaffman.
19 citations (Crossref) [2023-10-31] Place: Switzerland Mingrone, Alfred. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Kaffman, Ayal. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, United States. Kaffman, Arie. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, United States.
Keywords: Actual-HCA; Chora feeder; Intellicage system; PhenoTyper; Review; addiction; anxiety disorder; automated home cage monitoring; automation; behavioral science; cognition; depression; dept.psy; monitoring; nonhuman; peer-reviewed; preclinical study; psychiatry; rodent; rodents; translational research

Defense against outside competition is linked to cooperation in male-male partnerships - Hellmann, Jennifer K.; Stiver, Kelly A.; Marsh-Rollo, Susan; Alonzo, Suzanne H. (Behavioral Ecology, 2020)
Male–male competition is a well-known driver of reproductive success and sexually selected traits in many species. However, in some species, males work together to court females or defend territories against male competitors. Dominant (nesting) males sire most offspring, but subordinate (satellite) males are better able to obtain fertilizations relative to unpartnered males. Because satellites only gain reproductive success by sneaking, there has been much interest in identifying the mechanisms enforcing satellite cooperation (defense) and reducing satellite sneaking. One such potential mechanism is outside competition: unpartnered satellites can destabilize established male partnerships and may force partnered satellites to restrain from cheating to prevent the dominant male from replacing them with an unpartnered satellite. Here, we manipulated perceived competition in the Mediterranean fish Symphodus ocellatus by presenting an “intruding” satellite male to established nesting and satellite male pairs. Focal satellite aggression to the intruder was higher when focal satellites were less cooperative, suggesting that satellites increase aggression to outside competitors when their social position is less stable. In contrast, nesting male aggression to the intruder satellite increased as spawning activity increased, suggesting that nesting males increase their defense toward outside competitors when their current relationship is productive. We found no evidence of altered spawning activity or nesting/satellite male interactions before and after the presentation. These results collectively suggest that response to outside competition is directly linked to behavioral dynamics between unrelated male partners and may be linked to conflict and cooperation in ways that are similar to group-living species.
8 citations (Crossref) [2023-10-31] WOS:000537266400017
Keywords: Satellites; Symphodus ocellatus; alternative reproductive tactics; biological market theory; cooperation; cooperative behavior; defense mechanism; dept.psy; interspecific competition; intraspecific interaction; outside options; peer-reviewed; satellite male; sneak

Big five, linguistic styles, and successful online learning - Abe, J. (Internet and Higher Education, 2020)
With the tremendous growth in online classes and programs at institutions of higher education, conflicting claims are increasingly being made on media and blog sites about the personality types that are compatible with this new learning format. The relations between the Five Factor Model of Personality (FFM) and linguistic styles with measures of academic performance in fully online asynchronous classes were examined. Consistent with findings based on research in face-to-face classes, Conscientiousness, Openness to Experience, and Analytic Thinking were associated with academic success. There was no support for the views propagated on the internet that extraversion, introversion, or anxiety hinder or foster online learning. The most robust predictor of academic performance throughout the semester, independent of the personality variables, was the number of words students contributed to the online discussions. These finding are interpreted within the Community of Inquiry framework (CoI; Garrison, 2003) and future lines of research are suggested. © 2020 Elsevier Inc.
31 citations (Crossref) [2023-10-31] tex.ids: abeBigFiveLinguistic2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85078113247 type: Article
Keywords: Academic performance; Community of Inquiry framework (CoI); Community of inquiry; E-learning; Education computing; Five Factor Model Of Personality (FFM); Five-factor model of personality; LIWC; Linguistic analysis; Linguistics; Online learning; dept.psy; peer-reviewed

N400 amplitude, latency, and variability reflect temporal integration of beat gesture and pitch accent during language processing. - Morett, Laura M; Landi, Nicole; Irwin, Julia; McPartland, James C (Brain Research, 2020)
This study examines how across-trial (average) and trial-by-trial (variability in) amplitude and latency of the N400 event-related potential (ERP) reflect temporal integration of pitch accent and beat gesture. Thirty native English speakers viewed videos of a talker producing sentences with beat gesture co-occurring with a pitch accented focus word (synchronous), beat gesture co-occurring with the onset of a subsequent non-focused word (asynchronous), or the absence of beat gesture (no beat). Across trials, increased amplitude and earlier latency were observed when beat gesture was temporally asynchronous with pitch accenting than when it was temporally synchronous with pitch accenting or absent. Moreover, temporal asynchrony of beat gesture relative to pitch accent increased trial-by-trial variability of N400 amplitude and latency and influenced the relationship between across-trial and trial-by-trial N400 latency. These results indicate that across-trial and trial-by-trial amplitude and latency of the N400 ERP reflect temporal integration of beat gesture and pitch accent during language comprehension, supporting extension of the integrated systems hypothesis of gesture-speech processing and neural noise theories to focus processing in typical adult populations. Copyright © 2020 Elsevier B.V. All rights reserved.
8 citations (Crossref) [2023-10-31] Place: Netherlands Morett, Laura M. University of Alabama, United States. Electronic address: lmorett@ua.edu. Landi, Nicole. Haskins Laboratories, University of Connecticut, United States. Irwin, Julia. Haskins Laboratories, Southern Connecticut State University, United States. McPartland, James C. Yale University, United States.
Keywords: Adolescent; Adult; Beat gesture; Brain; Electroencephalography; Evoked Potentials; Evoked response variability; Female; Humans; Language; Male; N400; Pitch Perception; Pitch accent; Speech; Speech Perception; Temporal integration; Young Adult; adolescent; adult; article; brain; comprehension; controlled study; dept.psy; electroencephalography; event related potential; evoked response; female; gesture; human; human experiment; language; language processing; male; noise; peer-reviewed; physiology; pitch; pitch perception; speech; speech perception; videorecording; young adult

Motivation States for Physical Activity and Sedentary Behavior: Desire, Urge, Wanting, and Craving. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Bartholomew, John B; Gilson, Todd A; Ash, Garrett I; McKee, Paul C; Sinha, Rajita (Frontiers in psychology, 2020)
To better explain daily fluctuations in physical activity and sedentary behavior, investigations of motivation are turning from social cognitive frameworks to those centered on affect, emotion and automaticity, such as the Affect and Health Behavior Framework (AHBF), Integrated Framework and Affective-Reflective Theory (ART). This shift has necessitated: (a) re-examination of older theories and their constructs, such as drives, needs and tensions and (b) an inspection of competing theories from other fields that also attempt to explain dynamic changes in health behaviors. The Dynamical Model of Desire, Elaborated Intrusion Theory and others commonly share with AHBF the idea that human behavior is driven strongly by desires and/or the similar concepts of wants, urges, and cravings. These affectively-charged motivation states (ACMS) change quickly and may better explain physical activity behavior from one moment to the next. Desires for movement predominantly derive from negative but also positive reinforcement. Data from clinical populations with movement dysfunction or psychiatric disorders provides further evidence of these drivers of movement. Those with Restless Legs Syndrome, akathisia, tic disorders and exercise dependence all report strong urges to move and relief when it is accomplished. Motor control research has identified centers of the brain responsible for wants and urges for muscular movement. Models elaborated herein differentiate between wants, desires, urges and cravings. The WANT model (Wants and Aversions for Neuromuscular Tasks) conceptualizes desires for movement and rest as varying by magnitude, approach or avoidance-orientation (wants versus aversions) and as occupying independent dimensions instead of opposite ends of the same axis. For instance, one hypothetically might be in a state of both high desire for movement and rest simultaneously. Variations in motivation states to move and rest may also be associated with various stress states, like freezing or fight and flight. The first validated instrument to measure feelings of desire/want for movement and rest, the CRAVE Scale (Cravings for Rest and Volitional Energy Expenditure) is already shedding light on the nature of these states. With these advances in theory, conceptual modeling and instrumentation, future investigations may explore the effects of desires and urges for movement and sedentary behavior in earnest. Copyright © 2020 Stults-Kolehmainen, Blacutt, Bartholomew, Gilson, Ash, McKee and Sinha.
15 citations (Crossref) [2023-10-31] Place: Switzerland Stults-Kolehmainen, Matthew A. Bariatric and Minimally Invasive Surgery Program, Yale-New Haven Hospital, New Haven, CT, United States. Stults-Kolehmainen, Matthew A. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Blacutt, Miguel. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Bartholomew, John B. Department of Kinesiology and Health Education, The University of Texas at Austin, Austin, TX, United States. Gilson, Todd A. Department of Kinesiology and Physical Education, Northern Illinois University, DeKalb, IL, United States. Ash, Garrett I. Pain Research, Informatics, Multi-morbidities, and Education (PRIME), VA Connecticut Healthcare System, West Haven, CT, United States. Ash, Garrett I. Center for Medical Informatics, Yale School of Medicine, New Haven, CT, United States. McKee, Paul C. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Sinha, Rajita. Yale Stress Center, Yale School of Medicine, New Haven, CT, United States.
Keywords: conceptual analysis; dept.psy; desire; exercise; motivation; motivation states; peer-reviewed; physical activity; sedentary activity; urge for movement

Impact of enriched environment during adolescence on adult social behavior, hippocampal synaptic density and dopamine D2 receptor expression in rats - Gabriel, Paul; Mastracchio, Toni-Ann; Bordner, Kelly; Jeffrey, Rachel (Physiology & Behavior, 2020)
Environmental enrichment (EE) is one experimental manipulation that induces changes in the brain. However, it is important to distinguish between physical and social components of enrichment. To this end we established four groups of rats reared in different enriched environments during the adolescent period. Our results indicate heightened social memory and increased spine density in dentate gyrus specifically in socially enriched animals. Physical enrichment increased spine density in CA1. Dopamine D2 receptor expression in hippocampus was decreased across all enrichment conditions. Altogether, our results demonstrate differing effects of physical and social enrichment, supporting an important role for environment in synaptogenesis, behavior, and dopaminergic signaling. © 2020 The Authors
17 citations (Crossref) [2023-10-31] tex.ids: gabrielImpactEnrichedEnvironment2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089521109 type: Article
Keywords: Adolescence; Animals; Article; Dopamine; Environment; Environmental enrichment; Hippocampus; Memory; Rats; Receptors; Dopamine D2; Social Behavior; Social enrichment; Synapse density; animal; animal behavior; animal experiment; controlled study; dentate gyrus; dept.bio; dept.psy; dopamine 2 receptor; dopaminergic transmission; environment; environmental enrichment; female; hippocampal CA1 region; hippocampus; male; memory; nonhuman; peer-reviewed; priority journal; protein expression; rat; social behavior; spine; synapse; synaptogenesis

A preliminary investigation into collegiate student-athletes’ attitudes towards athletic trainers and sport psychology consultants - Ildefonso, Kenneth; Blanton, Jedediah; Durwin, Cheryl; Arvinen-Barrow, Monna; Kamphoff, Cindra (Journal of Sport, 2020)
To investigate if athletes’ attitudes toward athletic trainers and sport psychology consultants differ considering nature of athletic ability beliefs and previous experiences with these professionals; collegiate student-athletes (n = 114 male, n = 81 female, M age = 19.77, SD = 1.43) completed the Conceptions of the Nature of Athletic Ability Questionnaire-2 (Biddle, Wang, Chatzisarantis, & Spray, 2003), Attitudes Toward Athletic Trainers-Form (modified from the Attitudes toward Physiotherapist-Form; Arvinen-Barrow, Clement, & Bayes, 2012), and the Sport Psychology Attitudes Revised-Form (Martin, Kellman, Lavallee, & Page, 2002). Multiple analyses of variance revealed small statistically significant mean differences in attitudes considering ability beliefs, previous athletic training, and sport psychology experiences. Athletes with previous athletic training experience were less confident in their athletic trainer than those without such experience. In contrast, athletes with previous sport psychology experience were more confident in their consultant than those without such experiences. Results suggest athletes’ attitudes towards helping professionals may be partially influenced by subjective norms and expectations about the nature of such relationships.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

The fear of missing out at work: Examining costs and benefits to employee health and motivation - Budnick, Christopher J.; Rogers, Arielle P.; Barber, Larissa K. (Computers in Human Behavior, 2020)
The popular business media argues that the “fear of missing out” (FoMO) on work-related opportunities harms employees’ health and performance. Yet, these claims rely on the study of FoMO in college students in non-work contexts. Therefore, we explored workplace FoMO among employees across three studies. We first developed a measure and provided validation evidence for workplace FoMO among diverse employees (N = 324; Study 1) and MBA students (N = 223; Study 2). Using a third large employee sample (N = 300; Study 3), we tested whether workplace FoMO predicted health (i.e., work burnout and work well-being) and motivational outcomes (i.e., message-checking behaviors and work engagement). We also examined whether family-supportive organizational perceptions (FSOP) moderated these relationships. Results indicated that workplace FoMO is a distinct construct from other measures, including general FoMO. Workplace FoMO also predicted work burnout and message checking behavior, but not work well-being. Lower levels of FSOP strengthened the positive relationship between workplace FoMO and message checking behavior, but also produced a positive relationship between workplace FoMO and work well-being. Overall, FoMO appears to be relevant to the work context and predicts both employee well-being and behavior outcomes. © 2019 Elsevier Ltd
34 citations (Crossref) [2023-10-31] tex.ids: budnickFearMissingOut2020a, pop00228 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85073522410 tex.type: Journal article type: Article
Keywords: Behavioral research; College students; Costs and benefits; Employee health; Fear of missing out; Health; Job satisfaction; Motivation; Students; Technology use; Technology use at work; Well being; Work engagements; Work-related; article; burnout; controlled study; dept.psy; fear of missing out; human; major clinical study; motivation; peer-reviewed; perception; wellbeing; work engagement